2012
DOI: 10.1007/s00595-012-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

Rectoseminal vesicle fistula as a rare complication after low anterior resection: a report of three cases

Abstract: A rectoseminal vesicle fistula is a rare complication after a low anterior resection for rectal cancer, usually developing in the outpatient postoperative period with pneumaturia, fever, scrotal swelling or testicular pain. A diagnostic water-soluble contrast enema, cystography and computed tomography reveal a tract from the rectum to the seminal vesicle. Anastomotic leakage is thought to be partially responsible for the formation of such tracts. This report presents three cases of rectoseminal vesicle fistula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Some papers suggested that complicated fistulas with a large diameter, previous failed repair surgery, or previous irradiation are negative predictive factors for the successful closure of fistulas. However, the average diameter of the URF and the previous repair rate were not different between our groups, and previous irradiation was administered to only 1 patient in [2] . On the other hand, URF after radical prostatectomy for PC might be easier to cure because the prostate and seminal vesicle were previously removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers suggested that complicated fistulas with a large diameter, previous failed repair surgery, or previous irradiation are negative predictive factors for the successful closure of fistulas. However, the average diameter of the URF and the previous repair rate were not different between our groups, and previous irradiation was administered to only 1 patient in [2] . On the other hand, URF after radical prostatectomy for PC might be easier to cure because the prostate and seminal vesicle were previously removed.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of URF after RC surgery is not well known. Nakajima et al [2] reported 3 cases in more than 1,100 low anterior resections for RC and indicated an incidence of less than 0.3%. In the current study, 14 patients with persistent URF were aggregated, and half of the patients had a history of RC surgery and the other half had PC surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Complications following low rectal anastomosis include leak, abscess, fistulae and anastomotic stenosis. Seminal vesicle‐rectal (SV‐R) fistulation is a complication that is not commonly reported, and as such, there is no algorithm for the management of these patients . In the present review, risk factors that lead to the development of SV‐R fistula are highlighted, and management options for this uncommon and challenging morbidity are proposed.…”
Section: Introductionmentioning
confidence: 90%
“…SV‐R fistula is an extremely rare occurrence following low anterior resection for rectal cancer. Only 12 cases have ever been described in the literature . As such, there is no clear consensus to explain why they occur or which patients are at risk.…”
Section: Case Reportmentioning
confidence: 99%
“…Fistulae between the gastrointestinal and urogenital tracts are most commonly colovesical, with the aetiology including diverticular disease (65–75% of cases), cancer (10–20% of cases) and Crohn’s disease (5–7%) . There are very few cases of seminal vesicle‐rectal fistulae described, with only 13 individuals identified and none resulting in severe purulent epididymo‐orchitis requiring orchidectomy.…”
mentioning
confidence: 99%